STREPTOKINASE FOR ACUTE MYOCARDIAL INFARCTION IN THE ELDERLY - Qureshi, Azmat Ehsan; Jafri, Nasir Ali; Noeman, Ahmed; Yasmin, Samra; Khalil, Hamid (Journal of Ayub Medical College Abbottabad, 2014)
Background: Acute myocardial infarction is one of the leading causes of death in the elderly, however clinical data reveals a disproportionately lower use of thrombolytics because of fear of complications especially intracranial haemorrhage. Our objective was to evaluate the safety of most commonly used thrombolytic streptokinase in elderly patients presenting with acute myocardial infarction. Methods: This descriptive case series was conducted at Punjab Institute of Cardiology, Lahore from September to December 2012 (4 months). One hundred elderly patients presenting with acute myocardial infarction were randomly selected for the study keeping in view the inclusion and exclusion criteria. All patients were thrombolysed with streptokinase within 12 hours of onset of symptoms and were monitored and investigated for electrical, mechanical and biochemical complications. Results: Out of one hundred patients 77 (77%) were males and 23 (23%) were females. Mean age was 73.39±5.29 years. The two most common complications of streptokinase were hypotension (33%) and bleeding (19%). Major bleed occurred only in 3 (3%) patients. No patient developed intracranial haemorrhage. Other complications included arrhythmias (6%), allergic reactions (4%), raised LFTs (6%) and raised RFTs (7%). No patient died of streptokinase related complications. Conclusions: Use of streptokinase for acute myocardial infarction should not be discouraged in the elderly. Keywords: Acute myocardial infarction, Streptokinase, Thrombolytics